Therapeutic effect of fenofibrate for non-alcoholic steatohepatitis in mouse models is dependent on regime design - Wang, Xinxue; Luo, Jia; Lu, Zhuoheng; Fang, Shenzhe; Sun, Mengxia; Luo, Wenjing; Shen, Jianwei; Liu, Aiming; Ye, Hua (Frontiers in Pharmacology, 2023)
Background: Non-alcoholic fatty liver disease (NAFLD) is the leading cause of chronic liver diseases. In most cases, NAFLD progresses from benign steatosis to steatohepatitis (NASH), and then to cirrhosis. No treatment is currently approved for NAFLD/NASH in the clinic. Fenofibrate (FENO) has been clinically used to treat dyslipidemia for more than a half century, but its effects on NASH are not established. FENO’s half-life is quite different between rodent and human. The aim of this study was to investigate the potential of pharmacokinetic-based FENO regime for NASH treatment and the underlying mechanisms.Methods: Two typical mouse NASH models, methionine-choline deficient (MCD) diet-fed mice and choline-deficient, L-amino acid-defined, high-fat diet (CDAHFD)-fed mice, were used.MCD model was designed as therapeutic evaluation in experiment 1 and CDAHFD model was designed as preventive in experiment 2. Three doses of FENO (5, 25, 125 mg/kg), two times a day (BID), were administered to the above models. Serum markers of liver injury, cholestasis, and the histology of liver tissues were investigated. Normal mice were used as a model in experiment 3 for toxicity evaluation, Quantitative-PCR and Western Blot assays were used to investigate the inflammatory responses, bile acid synthesis as well as lipid catabolism.Results: Mice on the MCD and CDAHFD diets developed steatohepatitis as expected. In the MCD model, the therapeutic action of FENO (25 mg/kg·BID) and 125 mg/kg·BID on histopathology and the expression of inflammatory cytokines were comparable. In reducing macrophage infiltration and bile acid load, FENO (25 mg/kg·BID) was superior to 125 mg/kg·BID. In all the aspects mentioned above, FENO (25 mg/kg·BID) was the best among the 3 doses in the CDAHFD model. In both models, FENO (5 mg/kg·BID) showed little effect in hepatic steatosis and inflammation, neither the adverse effects. FENO (125 mg/kg·BID) aggravated liver inflammation, increased bile acid synthesis, and promoted the potential of liver proliferation. In toxicity risk assay, FENO (25 mg/kg·BID) treatment showed low potential to trigger bile acid synthesis, inflammation and hepatocyte proliferation. Conclusion: A new regime, FENO (25 mg/kg·BID) is potentially a therapeutic strategy for the NASH treatment. Translational medicine is warranted to prove its effectiveness in the clinic.